Institutional resilience amid structural neglect: state funding, educational quality, and governance strategies in a christian private school in eastern Indonesia - Julianus Labobar; Julya Pentury; Yakob Godlif Malatuny (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2026)
This study examines the institutional resilience of a Christian private school in Eastern Indonesia amid limited state support and structural inequality in educational governance. The research focuses on how the absence of public-school status and restricted government funding affect educational quality, institutional sustainability, and access to learning resources at Christian Theology Junior High School Marturia Sentani, Papua. A qualitative case study design was employed involving 10 teachers and 30 students as primary informants. Data were collected through in-depth interviews, field observations, and document analysis, and were analyzed thematically through data reduction, categorization, interpretation, and meaning construction. The findings reveal that the school has developed strong institutional capital through legal legitimacy, accredited academic status, adaptive leadership, a positive learning culture, and qualified teaching personnel. However, the institution continues to face structural challenges, including inadequate infrastructure, shortages of subject teachers, limited instructional media, and weak governmental support for Christian private education. In response, the school has implemented governance-strengthening strategies through teacher capacity development, collaborative organizational culture, standardized operational procedures, and institutional partnerships with local authorities. The study argues that educational quality in marginalized regions is shaped not only by formal state recognition but also by government regulatory support, institutional governance capacity, and social and institutional networks in education.